144 A PILOT STUDY TO BENCHMARK FRAILTY NEEDS IN AN ACUTE OLDER SURGICAL INPATIENTS. (25th October 2022) - Khan, I; Nor, MNBMD; Pillay, I
Abstract: Background: Evidence to support screening for frailty among acute surgical inpatients is limited. Our aim was to identify surgical inpatients on a general/vascular surgery ward with unmet, frailty-associated needs. Methods: From 01/03/2022 to 12/04/2022, all inpatients under a vascular/general surgery service in a model 4 hospital were screened for frailty using a modified THINKfrail tool. An abbreviated CGA ('little g'), to identify what matters to the patient, mobility and functional impairment, mood and mental state and medication review was performed and actions taken on the results. Results: 138 patients were admitted under the surgical teams during the study period. 30% (n=42) were over 70 years. 8% (n=11) screened positive for frailty, all of whom underwent a 'little g'. The mean (SD) age was 77 (4) years. 45% (n=5) were male. Identified needs were included abnormal 4AT in 50% (n=5), 3 of whom had no prior diagnosis of dementia. 45% had altered ADLs resulting in a reduced ability to dress or mobilise. 80% (N=9) required optimisation of mobility and/or physical function. 45% (n=5) had medication changes made. Conclusion: A simple modified THINKfrail tool can be implemented by surgical nurses to screen for patients who may need geriatric input. Most have physio and OT needs and 45-50% have undetected cognitive or medication related issues, detected by employing a 'little g'. Employing a ward-based frailty screen, followed by little g assessment is effective. This approach should be prospectively validated.